Be a Mom, a Web-Based Intervention to Promote Positive Mental Health Among Postpartum Women With Low Risk for Postpartum Depression: Exploring Psychological Mechanisms of Change - Monteiro, Fabiana; Pereira, Marco; Canavarro, Maria Cristina; Fonseca, Ana (Frontiers in Psychiatry, 2021)
Background: This study explored whether Be a Mom, a brief and unguided cognitive behavioral web-based intervention, was effective in promoting psychological processes (self-compassion, psychological flexibility, emotion regulation) among low-risk postpartum women. Effects of Be a Mom in psychological processes compared with a control group were examined at post-intervention and at four-months follow-up. Additionally, this work explored whether changes in psychological processes mediated improvements in positive mental health at postintervention. Methods: In total, 367 postpartum women presenting low risk for postpartum depression were randomly assigned to the intervention group (n = 191) or to a waiting-list control group (n = 176). Results: Compared with the control group, the intervention group reported significantly greater baseline to postintervention increases in self-compassion. No significant effects were found at the four-month follow-up. Multilevel mediation showed that self-compassion improvements significantly mediated improvements in positive mental health among the intervention group. No significant results were found for psychological flexibility or emotion regulation. Conclusions: This study suggests that Be a Mom has the potential to cultivate self-compassion among low-risk postpartum women and that this may be a key mechanism for promoting positive mental health in this context. Clinical trial registration: www.clinicaltrials.gov identifier: NCT04055974